Study on indoor and outdoor permeability coefficients and bacterial components, sources of fine particles in severe cold region of China. (April 2020) - Lv, Yang; Zhou, Yuwei; Chen, Xi; Zhao, TongKe; Liu, Tao; He, Xin; Liu, Jing; Ye, Xiao
Highlights: It obtained indoor and outdoor PM2.5 permeability coefficients, also bacterial community and source. The average permeability coefficient of fine particles in Harbin is similar to that in Mudanjiang during non-heating season. The dominant bacteria on fine particles is Proteobacteria, accounted for more than 95% in non-heating season. No matter which city in different season, their source proportions of indoor human and outdoor soil are larger than others. Abstract: To control severe air pollution and promote cities sustainable development in an old industrial base of severe cold region in China, it obtained indoor and outdoor PM2.5 permeability coefficients, also bacterial community and source by 16s rDNA gene sequencing technique and BLAST ( The Basic Local Alignment Search Tool ) source apportionment through long-term monitoring of residences in two typical cities of Heilongjiang Province (Harbin and Mudanjiang) in Northeast China during heating and non-heating season. The results showed that the average permeability coefficient of indoor and outdoor fine particles in Harbin is similar to that in Mudanjiang during non-heating season (Harbin: 0.7131, Mudanjiang: 0.7312) mainly due to natural ventilation. In heating season, Harbin (0.5325) was lower than that in Mudanjiang (0.6918) due to the differences in industrial characteristics and building tightness. The dominant bacteria on indoor and outdoor fine particles was Proteobacteria for two cities, accounted for more than 95 % in non-heating season, while for heating season were Proteobacteria, Firmicutes and Bacteroidetes, which were proportional different due to the different average permeability coefficients, intensities of ultraviolet rays and temperature. And no matter which city in different season, their source proportions of indoor human and outdoor soil are larger than others.